Breaking Default Bias: How Regulatory Choice Architecture Shapes Competition in Platform Ecosystems - Hermansyah (Legalis : Journal of Law Review, 2025)
This article examines how default bias and switching frictions reinforce platform dominance and whether regulatory interventions can reduce these barriers. The research employs a difference-in-differences framework combined with event-study analysis to measure the causal effects of DMA obligations on user switching. Data sources include browser adoption statistics, app store analytics, and compliance monitoring reports from the European Commission. Key outcome variables include browser switching rates, alternative browser market shares, and adoption of link-out billing systems. The introduction of DMA choice screens resulted in a marked increase in consumer switching, with browser switching rates rising from 8.5% to 13.2%, demonstrating the policy’s effectiveness in breaking consumer inertia associated with defaults and alternative browser shares increasing from 19.6% to 24.5%. Link-out billing adoption grew from 2.1% to 8.3%. Cross-country heterogeneity reveals that countries with high digital literacy and strong infrastructure, such as Germany and the Netherlands, saw stronger switching effects compared to southern European countries with entrenched default reliance. The discussion highlights the role of behavioral economics in designing effective choice screens, the challenges posed by dark patterns, and the comparative advantages of interoperability mandates over structural remedies in fostering sustained competition. The analysis underscores that interoperability lowers switching costs, enhances contestability, and incentivizes platforms to innovate, thereby benefiting consumers and promoting long-term market dynamism. The study concludes that ex ante regulatory mandates under the DMA are effective in reducing consumer lock-in and reshaping digital market dynamics. However, regulatory vigilance is essential to prevent circumvention through manipulative design practices. The findings contribute to ongoing policy debates on digital regulation, emphasizing the need for adaptive, user-centered governance frameworks that balance competition, innovation, and consumer welfare.